2018
DOI: 10.2478/jee-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat flow direction on solder ball interfacial layer

Abstract: This paper deals with the research of an intermetallic layer of SAC305 solder balls soldered from three directions of the heat flow in the ball-attach process for BGA package. From the point of view of the heat flow direction, the samples were soldered by infrared heating. The heat sources were placed on the top, bottom and both lateral sides of the BGA package. After the solder balls-attach process, a metallographic cross-section was performed, followed by selective etching to visualize the relief of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…However, the heating factor does not always play the decisive role, since it describes only the reflow phase of the soldering process. The IMC thickness is also influenced by the preheat phase, when the flux is activated, as shown in our previous work [25], by the direction of the heat flow [26] and also by the post reflow cooling rate [27].…”
Section: Intermetallic Layer Growthsupporting
confidence: 55%
“…However, the heating factor does not always play the decisive role, since it describes only the reflow phase of the soldering process. The IMC thickness is also influenced by the preheat phase, when the flux is activated, as shown in our previous work [25], by the direction of the heat flow [26] and also by the post reflow cooling rate [27].…”
Section: Intermetallic Layer Growthsupporting
confidence: 55%
“…Many studies observed and confirmed that the formation of voids strongly depends on the reflow soldering parameters, including preheating zone, peak temperature, and soaking time [7]. The direction of heat flow and cooling can also have an influence on the properties and structure of the resulting solder joints and voids' formation, which was confirmed by [8][9][10].…”
Section: Introductionmentioning
confidence: 96%